Recent developments in optical fibre based optoelectronic oscillators - Ironside, Charles; Haji, M.; Kelly, A.; Figueiredo, J. (Engineers Australia, 2014)
The paper reports recent progress on new types of low noise and high spectral purity optoelectronic oscillators operating at optical wavelengths around 1550nm and radio frequencies (RF) up to 40GHz with RF linewidths <1kHz.